Modelo para avaliar o impacto dos treinamentos do Instituto Federal do Amazonas - IFAM - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
This study aimed to develop a model to assess the impact of funded training to technical administrative staff of IFAM / Campus of Manaus downtown and Rectory, in the years 2010 and 2011. Therefore, the research set up in a case study, qualitative and quantitative scope. Data collection was conducted through a questionnaire applied to 42 technicians and 15 managers. The data collected were subjected to statistical treatment which involved measures of mean, standard deviation and relative frequency, in order to compare the perceptions of the groups evaluated; and, from the collection instrument there was built the model proposed on the hereby research. The theoretical work included nine models of training evaluation. Among them, the most suitable for the development of the model presented in the work were the studies of Kirkpatrick (1976) and Hamblin (1978), Borges-Andrade (MAIS model) developed in 1982 and Abbad (IMPACT model) in 1999. The criteria used to assess the impact of the training were: behavior in office, learning, performance, support to learning and work transfer. The results obtained showed that the requirement better assessed by technicians was the impact of training on performance in office, while for the head offices it referred to the impact of training on the job. There were noted some difficulties pointed out by technicians for participating in training at IFAM/CMC namely: supply, release, unavailability, quality and knowledge transfer. Results also allowed the verifying of the effectiveness of the training which the technicians took part.
Keywords: Modelos de avaliação; Técnicos e chefias; Impacto do treinamento.; Models of training; Technicians and managers; Impact of training.; ENGENHARIAS: ENGENHARIA DE PRODUÇÃO